CHROMATIC NUMBER TO THE TRANSFORMATION (G---) OF K(1,n) AND K(m,n) - John, B. Stephen (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
Let be an undirected simple graph. The transformation graph ofG is a simple graph with vertex set in which adjacency is defined as follows: (a) two elements in are adjacent if and only if they are non-adjacent in (b) two elements in are adjacent if and only if they are non-adjacent in and (c) an element of and an element of are adjacent if and only if they are non-incident in .In this paper, we determine the chromatic number of Transformation graph for Star and Complete Bipartite graph. Keywords: Star Graph, Complete Bipartite Graph, Chromatic Number, Transformation Graph